Comment peut-on être Indien et citoyen ? - Maud Yvinec (Caravelle)
Between 1826 and 1854, the contribución de indígenas inspired by the colonial tribute reinstates in Peru a distinction between Indian and non-Indian populations which appears to contradict the granting of citizenship not only to creoles and mestizos but also to natives during Independence. The following article will try to shed new light on this fundamental ambiguity by illustrating the complexity of official discourse : in spite of its claims to institute a uniform society, there are numerous cases in which officials still seem to consider the Indians as a distinct entity and one can even find instances where these grand principles are completely undercut by local authorities.